2023
DOI: 10.1007/jhep03(2023)166
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the magnetic dipole moments of $$ {T}_{QQ\overline{q}\overline{s}} $$ and $$ {T}_{QQ\overline{s}\overline{s}} $$ states in the framework of QCD light-cone sum rules

Abstract: Motivated by the recent observation of the tetraquark $$ {T}_{cc}^{+} $$ T cc + , we investigate the magnetic dipole moments of the possible single and double strange partners, $$ {T}_{QQ\overline{q}\overline{s}} $$ T QQ q ¯ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Focusing on this state, in Ref. [93], J P = 1 + T Q Q q s and T Q Q s s states are studied as diquark-antidiquark tetraquarks and magnetic moments are calculated with using heavy axial vector diquark-light scalar antidiquark type current denoted as J 1 , heavy scalar diquark-light axial vector antidiquark type current denoted as J 2 , heavy tensor diquark-light axial vector antidiquark type current denoted as J 3 and heavy vector diquark-light pseudotensor antidiquark type current denoted as J 4 . According to their work, J 1 gives μ = (−0.46 ± 0.07)μ N , J 2 gives Our results are compatible with this work.…”
Section: Tetraquarks With Strangeness-one (S = −1)mentioning
confidence: 99%
“…Focusing on this state, in Ref. [93], J P = 1 + T Q Q q s and T Q Q s s states are studied as diquark-antidiquark tetraquarks and magnetic moments are calculated with using heavy axial vector diquark-light scalar antidiquark type current denoted as J 1 , heavy scalar diquark-light axial vector antidiquark type current denoted as J 2 , heavy tensor diquark-light axial vector antidiquark type current denoted as J 3 and heavy vector diquark-light pseudotensor antidiquark type current denoted as J 4 . According to their work, J 1 gives μ = (−0.46 ± 0.07)μ N , J 2 gives Our results are compatible with this work.…”
Section: Tetraquarks With Strangeness-one (S = −1)mentioning
confidence: 99%
“…The use of LCSR to obtain electromagnetic properties for doubly-heavy baryons, tetraquarks and pentaquarks is illustrated in refs. [39][40][41][42][43][44][45][46][47].…”
Section: Motivationmentioning
confidence: 99%
“…In the language of magnetic moments, changing the basis of the hadron also changes its internal structure, potentially leading to significant changes in the results. Different interpolating currents have been utilized for tetra-and pentaquarks to extract their magnetic moment in [41,75,76]. The results showed that the magnetic moments varied significantly depending on the diquark structures employed.…”
Section: Jhep05(2024)301mentioning
confidence: 99%
“…The use of LCSR to obtain electromagnetic properties for doubly-heavy hadrons is illustrated in Refs. [37][38][39][40][41][42][43][44][45].…”
Section: Motivationmentioning
confidence: 99%
“…In the language of magnetic moments, changing the basis of the hadron also changes its internal structure, potentially leading to significant changes in the results. Different interpolating currents have been utilized for tetraand pentaquarks to extract their magnetic moment in [39,58,59]. The results showed that the magnetic moments varied significantly depending on the diquark structures employed.…”
Section: Numerical Illustrationsmentioning
confidence: 99%